Prevalence of pyoderma in dogs in the city of Poltava - Кlymas, І. (Scientific Progress & Innovations, 2025)
In this work, a retrospective analysis of cases of skin diseases, in particular pyoderma in dogs, was carried out in 2022–2024. The research focuses on the prevalence, clinical characteristics, and seasonal dynamics of skin disorders, with particular attention to pyoderma, which was identified as the most common dermatological condition among the examined patients. A total of 1670 dogs were evaluated, and 417 cases of skin diseases (approximately 25 %) were diagnosed. A yearly increase in both the absolute number and proportion of dermatological cases was observed, indicating either a rising prevalence or improved diagnostic accuracy. Pyoderma accounted for the largest share of skin conditions (41,2 %), with the acute (60,5 %), superficial (84,3 %), and localized (75 %) forms being most common. The dominant clinical forms included superficial folliculitis (56,5 %), papulovesicular dermatitis (20 %), and interdigital pyoderma (16,5 %). Deep pyoderma was less frequent and was primarily represented by traumatic pyodermatitis, pododermatitis, and acne. Lesions were most commonly localized to the head, sacral region, and ventral abdomen. A marked seasonal pattern was established, with peak incidence in autumn (September to November), likely due to climatic changes, increased humidity, and decreased skin immune defense in that period. Age-related analysis revealed the highest incidence in dogs aged 8 months to 2 years, with a gradual decline thereafter. Breed analysis showed that skin diseases affected dogs of various breeds regardless of coat type, although a slight predominance was noted in long-haired breeds such as German Shepherds, Yorkshire Terriers, and Shih Tzus. These findings have practical significance for improving clinical awareness, developing more accurate diagnostic algorithms, and designing targeted prevention and treatment protocols that consider seasonal, age-related, and breed-specific risk factors.